2019
DOI: 10.1021/jacs.9b00485
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Salphen-based Covalent–Organic Frameworks as Catalytic Antioxidants

Abstract: The development of three-dimensional (3D) functionalized covalent organic frameworks (COFs) is of critical importance for expanding their potential applications. However, the introduction of functional groups in 3D COFs remains largely unexplored. Herein we report the first example of 3D Salphenbased COFs (3D-Salphen-COFs) and their metal-containing counterparts (3D-M-Salphen-COFs), the later being further used as catalytic antioxidants. These Salphen-based COFs exhibit high crystallinity and specific surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
143
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(155 citation statements)
references
References 43 publications
3
143
0
Order By: Relevance
“…[22,23] Thus,w es peculated that salen-containing frameworks and polymers may display good electrocatalytic OER performance, because salen-CMPs combine the rigid conjugated porous structure of CMPs and the intrinsic electrocatalytic activity of the salen moiety. [24][25][26][27][28][29][30] In this work we have demonstrated the ability of salen-containingp olymers to act as electrocatalysts for the first time. The electrochemical test results showed that the catalyst salen-CMP-Fe-3 showed the highest OER activity.W hen loaded onto glass carbon electrodes, the prepared salen-CMP-Fe-3 electrodes demonstratedas mall Tafel slope of 63 mV dec À1 and an overpotentialo f2 38 mV at 10 mA cm À2 in 0.1 m KOH.…”
Section: Introductionmentioning
confidence: 80%
“…[22,23] Thus,w es peculated that salen-containing frameworks and polymers may display good electrocatalytic OER performance, because salen-CMPs combine the rigid conjugated porous structure of CMPs and the intrinsic electrocatalytic activity of the salen moiety. [24][25][26][27][28][29][30] In this work we have demonstrated the ability of salen-containingp olymers to act as electrocatalysts for the first time. The electrochemical test results showed that the catalyst salen-CMP-Fe-3 showed the highest OER activity.W hen loaded onto glass carbon electrodes, the prepared salen-CMP-Fe-3 electrodes demonstratedas mall Tafel slope of 63 mV dec À1 and an overpotentialo f2 38 mV at 10 mA cm À2 in 0.1 m KOH.…”
Section: Introductionmentioning
confidence: 80%
“…In 2019, Fang and coworkers reacted halogenated orthophenylene diamines with Mastalerz's tetraphenylmethanebased tetrakis-salicylaldehyde under solvothermal conditions and obtained the highly crystalline COFs JUC-508 (Hal ¼ F) and JUC-509 (Hal ¼ Cl) (Scheme 13). 124 These networks retained their crystallinity after complexation with Mn 2þ , Cu 2þ , and Eu 3þ ions. PXRD analyses in combination with modeling revealed for all COFs noninterpenetrated networks of a dia topology.…”
Section: D-salen and Salphen Polymersmentioning
confidence: 92%
“…PXRD analyses in combination with modeling revealed for all COFs noninterpenetrated networks of a dia topology. 124 When an extended tetraphenylmethane core with one more phenyl group 122 or a siliconcentered analogue was used, sevenfold interpenetrated salphen COFs resulted, again with the dia topology (Scheme 14). 125 In this case, an in-situ metalation upon condensation in addition to the postmetalation of presynthesized COFs gave networks with high degrees of crystallinity.…”
Section: D-salen and Salphen Polymersmentioning
confidence: 99%
See 2 more Smart Citations